Evolução estrutural da Bacia do Amazonas e sua relação com o embasamento - WANDERLEY FILHO, Joaquim Ribeiro (Universidade Federal do Pará, 2019)
This dissertation presents some aspects concer- ning the structural evolution of the Amazon basin and discusses the role of the Pre-Cambrian structures in the development of its architeture. The Pre-Cambrian record comprises strutures re- lated to two main thermal-tectonic events. The oldest one, Archean age, is responsible for the installation of granitic- greenstone terrains, and also the formation of shear belts composed of high grade metamorphic rocks. This event controlled the formation of the basic structural lineaments, trending Nw- SE, NE-SW and E-W. The second event, in the eastern Amazon re- gion, caused the development of NW-SE and WNW-ESE normal faults and NE-SW transfer faults related to an extensional NE-SW proterozoic axis giving rise to the formation of several basins of which, Cachimbo Graben is the most remarkable one. The structural evolution of the Amazon basin throug Phanerozoic time is strongly related to the geometry of the Pre-Cambrian structures. The installation of the Amazon basin is related to cyclic opening and closing of the Iapetus ocean during Paleozoic time. During this cycle, ancient weakness zones tren- ding NE-SW and NW-SE were reactivated as normal and transfer faults respectively. The movements associated to the transfer faults compartmentalized the basin into four distinct structural blocks, of which the compartmental zone of Purus (Purus Ar- ch) isa special example. The Purus arch separates the Amazon basin to the East from Western Solimões basin. Its origin is related to reactivation of normal faults of the Cachimbo Graben. The fragmentation of the Gondwana megacontinent, during mesozoic time, is witnessed in the Amazon basin by the following features: a) NE-SW and NNE-SSW normal faults; b) Nw- SE transfer faults; c) ENE-WSW wrench faults and d) igneous and sedimentary infill. During Cenozoic time, the Amazon basin and adjacent zones suffered effects of stress that generated essencially dextral whrench faults.